SUBJECT SCOPE AND ARTISTRY OF N. FOZILOV’S STORIES - Musayeva Shakhlo Kuhratovna (Scholar Express Journal, 2023)
As a result of this small research, we have considered the comments on the theme and art of the stories of Nasir Fazilov, one of the great representatives of Uzbek children's literature.
Keywords: story; household stories; prototype; image